2006
DOI: 10.1002/pi.2010
|View full text |Cite
|
Sign up to set email alerts
|

Stereocomplexed polylactides (Neo‐PLA) as high‐performance bio‐based polymers: their formation, properties, and application

Abstract: Polymeric materials prepared from renewable natural resources are now being accepted as ''bio-based polymers'', because they are superior to the conventional petroleum-based polymers in reducing the emission of carbon dioxide. Among them, poly(L-lactide) (PLLA) prepared by fermentation and polymerization is paid an immediate attention. Although PLLA exhibits a broad range of physico-chemical properties, its thermal and mechanical properties are somewhat poorer for use as ordinary structural materials. For impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
325
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 414 publications
(332 citation statements)
references
References 194 publications
(263 reference statements)
6
325
0
1
Order By: Relevance
“…When the chain length of mbPDLAs increases, the value sharply increases, where an increase of 1 and 2 orders of magnitude is observed in mbPDLA201 and mbPDLA501, respectively. This reflects a formation of stronger interaction, i.e., hydrogen bonding, between the 2 stereoconstituents [2,47,48]. A sharp decrease in the values is observed when the structure melts.…”
Section: Rheological Properties Ofmentioning
confidence: 95%
See 2 more Smart Citations
“…When the chain length of mbPDLAs increases, the value sharply increases, where an increase of 1 and 2 orders of magnitude is observed in mbPDLA201 and mbPDLA501, respectively. This reflects a formation of stronger interaction, i.e., hydrogen bonding, between the 2 stereoconstituents [2,47,48]. A sharp decrease in the values is observed when the structure melts.…”
Section: Rheological Properties Ofmentioning
confidence: 95%
“…Tin(II) octoate catalyst, Sn(Oct) 2 , was purchased from Wako (Japan). Glycidol was purchased from Aldrich (USA) and used as received.…”
Section: Experimental 21 Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Stereocomplexation between PLLA and its enantiomer poly(D-lactide) (that is, poly(D-lactic acid) or PDLA) can yield biodegradable materials having superior mechanical performance and resistance to hydrolytic and thermal degradation relative to pure PLLA and PDLA. [16][17][18][19][20] Poly(2-hydroxybutyrate) (that is, poly(2-hydroxybutanoic acid) or P(2HB)) is a biodegradable polymer with the structure of a poly(lactide) (that is, poly(lactic acid) or PLA) in which methyl groups are substituted with ethyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, the long processing time in the crystallization-induced mixing and the low polymer concentration used in the electrospinning may retard the processabilities. Recently, we demonstrated that stereoblock-type PLAs (sb-PLA) consisting of PLLA and PDLA sequences can easily form the sc crystals with little hc crystallization [13][14][15][16][17][18][19][20][21], because they ought to have a mixing state of the enantiomeric PLLA and PDLA blocks in molecular level. Furthermore, we showed that the sbPLAs can efficiently be formed by spontaneous DielsAlder coupling of PLLA and PDLA prepolymers having dienophile (maleimide) and diene (anthracene) terminals, respectively [21].…”
Section: Introductionmentioning
confidence: 99%